PENGARUH PENDEKATAN REALISTIC MATHEMATICS EDUCATION TERHADAP KEMAMPUAN LITERASI MATEMATIS SISWA PADA SOAL CERITA MATERI PENJUMLAHAN KELAS I SDN 61 BANDA ACEH - Saumiana, Afra; Subhananto, Aprian; Marvida, Tria (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the application of the Realistic Mathematics Education (RME) approach on students’ mathematical literacy ability in addition material for first-grade students at SDN 61 Banda Aceh. This study was motivated by the low ability of students in understanding word problems, translating problems into mathematical models, and performing addition operations. This research employed a quantitative approach using a one-group pretest-posttest design. The research subjects consisted of 27 students. Data collection techniques included tests and documentation. Data analysis was conducted through normality testing, hypothesis testing using the Paired Sample t-Test, and N-Gain testing. The results showed a significant difference between pretest and posttest scores with a significance value of < 0.05, indicating that the application of the Realistic Mathematics Education approach had an effect on students’ mathematical literacy ability. The N-Gain test results showed an average score of 0.5047, which was categorized as moderate. Therefore, the Realistic Mathematics Education (RME) approach has an effect on students’ mathematical literacy ability in addition material.